Integrating microbial electrolysis cell based on electrochemical carbon dioxide reduction into anaerobic osmosis membrane reactor for biogas upgrading. (15th February 2021) - Gao, Tianyu; Zhang, Hanmin; Xu, Xiaotong; Teng, Jiaheng
Highlights: A novel AnOMBR-MEC system was constructed for biogas upgrading. CO2 produced from biogas was reduced to formate by SnO2 Nps electrocatalytic cathode in the MEC. The final methane content of >90% in the biogas was achieved when 1.2 V was supplied at MEC. Methanobacterium converted H2 and formate to methane at saline condition. Abstract: It has been reported that anaerobic osmosis membrane bioreactors have the potential for energy recovery since dissolved methane was almost rejected by commercial forward osmosis membranes. Notwithstanding, upgraded biogas has to be achieved by removing as much carbon dioxide as possible. In this study, a novel anaerobic osmotic membrane bioreactor-microbial electrolysis cell (AnOMBR-MEC) system was developed for simultaneous biogas upgrading and wastewater treatment. The AnOMBR-MEC elicited an excellent and stable soluble chemical oxygen demand and phosphorus removal. As the experiment progressed, unwanted carbon dioxide produced from biogas was reduced to formate using a SnO2 nanoparticles electrocatalytic cathode in an electrocatalytic-assisted MEC, with the highest faradic efficiency of formate being 85% at 1.2V. Compared to AnOMBR, the methane content increased from 55% to 90% at the end of operation and methane yield experienced a1.6-fold increment in the AnOMBR-MEC. Microbial community analysis revealed that hydrogenotrophic methanogens (e.g. Methanobacterium and Methanobrevibacte r) converted the produced H2 and formate to methane at saline conditions. These results have demonstrated an efficient strategy based on the integration of an electrocatalytic-assisted MEC into AnOMBR for upgrading biogas, enhancing methane yield and wastewater treatment. Graphical abstract: Image, graphical abstract